Guideline adherence is associated with long-term all-cause mortality in patients after an acute coronary syndrome. (25th November 2020) - Farmakis, I.T; Zafeiropoulos, S; Pagiantza, A; Boulmpou, A; Arvanitaki, A; Nevras, V; Tampaki, A; Markidis, E; Papadimitriou, I; Karvounis, H; Giannakoulas, G
Abstract: Background/Introduction: Guideline-directed medical therapy (GDMT) remains the mainstay in the long-term management of patients after an acute coronary syndrome (ACS). Data on the association of adherence to GDMT with clinical outcomes are scarce. Purpose: To assess the adherence to GDMT and its relation to all-cause mortality in a population of patients after an ACS. Methods: In this post-hoc analysis of the prospective, randomised IDEAL-LDL trial (NCT02927808) we analyzed data of 360 ACS patients discharged from a cardiology clinic. Median follow-up period was 35.9 (IQR 25.7–41.6) months. GDMT was assessed at discharge and at the 1-year follow-up, at which time data was collected by telephone interviews or ambulant visits. GDMT was defined as compliance with secondary prevention therapies (statin, antiplatelet, b-blocker, angiotensin-converting enzyme inhibitor (ACE-i) or angiotensin II receptor blocker (ARB)), as per their respective indication in the 2017 STEMI and 2015 NSTE-ACS ESC Guidelines. Extended follow-up data for mortality was collected from the national health insurance electronic prescription system. Results: Median age of the entire cohort was 60 (IQR-53–71) years, 18.6% were female and 55.6% suffered a STEMI. At discharge, 342 patients (95%) received statins, 331 (91.9%) proper antithrombotic therapy (86.4% on dual antiplatelet therapy (DAPT), 2.5% on antiplatelet plus anticoagulant and 3% on triple therapy), 309 (85.8%) β-blockers and 217 (60.3%) ACE-i or ARB. GDMT at discharge was prescribed to 272 (75.6%) patients. The 1-year mortality rate was 4.7% (IQR, 2.5–6.9) and there was no mortality benefit for GDMT (HR=0.77 95% CI 0.27 - 2.2) (Figure 1a). At the one-year follow up, 323 (94.2%) of 343 alive patients received statin treatment (72.4% of which a high-intensity statin), 330 (96.2%) any antithrombotic therapy (59.8% on DAPT, 5.2% on any anticoagulant), 263 (76.7%) a β-blocker and 194 (56.6%) an ACE-I or ARB. GDMT at one-year follow up was prescribed to 248 (72.3%) patients. Beyond one year, all-cause mortality was significantly reduced in patients receiving GDMT adjusted for age, STEMI, revascularization with percutaneous coronary angioplasty, history of diabetes mellitus and arterial hypertension. (1.6% vs 9.5%, aHR 0.3 95% CI 0.08 - 0.92) (Figure 1b). Conclusions: Adherence to GDMT remains stable one year after an ACS. GDMT was associated with a significant decrease in long-term mortality, but not associated with one-year mortality. Funding Acknowledgement: Type of funding source: None